Influência da fuligem da queima de palha de cana-de-açucar na presença de HPA em hortaliças de consumo humano - Sugauara, Lucy Elaine [UNESP] (2014)
The PAH are a class of organic contaminants which are formed in burning of sugarcane and fossil fuel. The physicochemical properties are associated with their affinity for fine particulate matter and can therefore be transported over long distances in a short time depending on the weather. The PAH have characteristics of mutagenicity, carcinogenicity and endocrine disruption, because of these characteristics they are substances that have earned interest of researchers in the evaluation of human exposure via differents routes of uptake, and currently the dietary is the less explored. This study aimed to optimize and validate a method for the determination of PAH in vegetables and evaluate the presence of these substances in lettuce , kale and arugula, in locations with and without the influence of sugarcane burning (Araraquara and Itu). The optimized and validated method in this work involves extraction by ultrasound bath and detection by HPLC/FLU, also has acceptable values of LOD and LOQ in accordance with the European Union , 0.3 and 0.9 μg kg- 1 respectively , and the CV (<11.6%) and recovery values (70 ~ 119 %), are also in accordance to the values recommended by ANVISA . Samples of lettuce , arugula and kale grown in two different cities on three sites , Araraquara (rural and urban areas) and Itu (urban area) corresponding to the harvest period (August 2012) and sugarcane off season (March 2013) were analyzed. Concentrations of PAH found in these vegetables were below the levels reported in the literature in leaves of different plant species . However, when considering the intake of 200g/day, half the daily intake of fruits and vegetables recommended by WHO (World Health Organization ) it is inferred that the amount of PAH ingested in this way corresponds to a High exposure diet with MOE ( Margin of exposure) < 10 000 near the limits considered worrisome by the European Union.